Internship Reports and Monograph entitled "Biomimetic-coated PLGA nanoparticles for cancer treatment and diagnosis" - Faria, Marta Filipa da Costa (2022)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia